Perfil químico e de minerais do óleo vegetal da semente de Camu-camu (Myrciaria dubia (HBK) Mc Vaugh) Mytaceae - Filho, Diógenes (2016)
Camu-camu The (Myrciaria dubia HBK McVaugh) is native to the Amazon and occurs in areas of wetlands. In Roraima, the native fruit is known as caçari. Its high content of vitamin C and antioxidants composition has designed the fruit to the leading position in recent research. This work comprises a vegetable oil chemical analysis of fruit samples of seeds harvested in Caçari Beach on the shores of Rio Cauamé in the city of Boa Vista, Roraima. Seeds, was extracted the dark green oil yield 2.88%. The study provided, through Nuclear Magnetic Resonance spectra Hydrogen (H1) and carbon (C13) physico-chemical properties of the oil and the composition of major fatty acids. Iodine Index (II) 55.39 mg I2 / g; Saponification index (SI) 178.14 mg KOH / g; Acid Number (IA) 1.46%; Relationship hydrogen Olefinic / Aliphatic (Ro, a) 0.361; Average Molecular Mass (MM) 934.16 g / mol were obtained from the calculations in the computer program Protoleos. The analysis of the carbon-13 spectrum signals shifts confirmed the presence of functional groups of fatty acids and unsaturation to the corresponding unsaturated fatty acids. The percentage of linolenic acid (ω-3) measured was 0.43%, linoleic acid (ω-6) 12.02% Oleic (ω-9) 62.49% and 25.10% saturated fatty acids. It was found that the oil camu-camu is not for consumption in the human diet and it makes up high antioxidant potential when compared to other vegetable oils. It is also confirmed that the Camu Camu seed-presenting low levels of oleossomos, therefore classified as starchy seed, due to its high starch reserves. The quantitative mineral analysis by ICP-OES technique disclosed concentration ranges of elements: K, Na, P, Si (> 100 ppm); Mg, S (10 to 100 ppm) and Ti (<100 ppm). The Protoleos program proved to be a useful tool for calculating the determination of physicochemical properties and composition of major fatty acids. The antioxidant activity by the DPPH method, shows that oil camu-camu has a high percentage antioxidant (IC50 = 114,72 μg.mL-1), with increasing concentration. The infrared analysis enabled the recognition of functional groups present in fixed vegetable oils. The results contribute new information to the literature on seed oil, Camu-Camu extract, and concentrations of minerals.